Investigation of sub-10nm cylindrical surrounding gate germanium nanowire field effect transistor with different cross-section areas. (May 2017) - Bayani, Amir Hossein; Dideban, Daryoosh; Voves, Jan; Moezi, Negin
Abstract: In this paper, germanium nanowires (GeNWs) with different cross-sectional areas are considered as the channel of a cylindrical surrounding gate field effect transistors (CSG-FETs) and the electronic properties of them are calculated through the density functional method and Slater-Koster (SK) tight binding model. The corresponding transistor parameters are obtained using Non-equilibrium Green's function (NEGF) combined by SK model. We find that SK model predicts the well-nigh same bandgap value compared to meta-GGA-DFT approximation, while GGA-DFT underestimates the value of the bandgap. CSG-GeNW-FETs Transistor figure of merit shows a supreme Ion /Ioff ratio which is equal to 10 12 for one of the considered structures with a circular cross-section. The obtained sub-threshold swing (SS) values for the FETs illustrate an increment trend when the supercell size of the germanium nanowire increases whereas the transconductance and ON-current of the FETs decrease when the GeNW supercell size scales down due to the declining of the density of states and electron transmission spectrum. Highlights: Germanium nanowires (GeNWs) with different cross-sectional areas are considered as the channel of a CSG-FET. CSG-GeNW-FET shows a supreme Ion /Ioff ratio which is equal to 10 12 . Three different methods consisting of PBE-GGA, MGGA and Slater-Koster model were used to calculate the bandstructures. ON- current increased when the supercell size of the GeNW was increased while the OFF-current decreased when it was scaled down. The subthreshold swing (SS) value and ION /IOFF ratio showed that 66-circular CSG-GeNW-FET has a better transistor performance.